RESEARCH OF INCLUSIVE COMPETENCE OF PEDAGOGICAL UNIVERSITY STUDENTS (EDUCATION IN THE 21ST CENTURY, 2023)
This article deals with the issue of the formation of inclusive competence of pedagogical university students. The analysis of scientific literature on the problem allowed revealing the essence of students’ inclusive competence – future teachers, revealed its relevance and showed that not enough attention is paid to its formation.The purpose of the study is to determine the level of formation of inclusive competence of pedagogical university students in the process of their professional training.Based on the goal, during the organization and conduct of the study, a range of specific tasks was solved.The first task was to study modern psychological and pedagogical literature on inclusive education and teacher training for its implementation. The solution of the first task also involved the analysis of existing theoretical approaches to the disclosure of the essence of the concept of "inclusive competence". The views of modern scientists on its interpretation were considered, structural components were highlighted. In this study, inclusive competence was defined as a component of a teacher's professional competence and was considered as an integrative personal education that allows him to implement professional and pedagogical functions, taking into account the peculiarities of inclusive practice. The components of inclusive competence of pedagogical university students are motivational-personal, cognitive and activity.To determine the current level of inclusive competence of students, the levels and criteria of this professional quality of future teachers (motivational, personal, cognitive and activity) were determined.In the course of the study, it was found that the majority of students have an inclusive competence formed insufficiently. Future teachers are experiencing serious difficulties in organizing joint education of children with normotypic development and children with disabilities. Hence, there is a need to develop and implement a model of the process of formation of inclusive competence in the practice of university training of teaching staff.
Keywords: professional competence; inclusive competence; student; future teacher; higher pedagogical education